Strategies to enhance the utilization of digital health in early detection and treatment of pre-eclampsia by gravid women in Emalahleni Local Municipality, Mpumalanga Province - Ngwenya, Nxolisi Welcome (My University, 2023)
Background: Gestational Hypertension and Pre-Eclampsia are the most prevalent conditions in Sub-Saharan Africa leading to undesirable perinatal and maternal outcomes. In South Africa, a high rate of maternal death was noted due to Pre- Eclampsia. However, the use of digital maternal health in South Africa has become of significance for the reinforcement of health care. Digital health initiatives such as mobile health initiatives were developed to improve better access to communities in low and middle-income countries. The implementation and practices of digital health seem to be growing and expandable to achieve the Universal Health Coverage goals in the provision of care to all globally and nationally. Purpose: To develop strategies to enhance the utilization of digital health in the early detection and treatment of Pre-Eclampsia by gravid women in Emalahleni Local Municipality, Mpumalanga Province. Methodology: A mixed convergent parallel research method was adopted in this study. In this study, the data was collected using quantitative and qualitative strands. The quantitative data was collected from midwifery practitioners using self-developed Likert scale questionnaires with a total of 64 items. The questionnaires were administered to 109 midwifery practitioners and the data was analyzed using descriptive statistics. The qualitative data was collected from the 10 gravid women using semi-structured one-on-one interviews and was analyzed using Tesch open coding method. A pilot study was conducted before conducting the main study to measure the validity and reliability of the questionnaire and interview guide. Thereafter the findings were merged to determine the extent to which they converge, diverge, and correlate. The integrated findings informed the development of the strategies. Thereafter a McKinsey 7s Model along with Appraisal of Guidelines for Research & Evaluation II guided the development of the strategies to enhance utilisation of digital health. The ethical standards were adhered to in this study. Ethical approval was obtained from Turfloop Ethics Committee (TREC/81/2022:PG). Results: The integrated findings showed that there are inconsistencies on the knowledge and importance of digital health utilization in the management of Pre- Eclampsia. Moreover, there are barriers to the utilization of digital health such as lack of awareness, shortage of digital and human resources, power supply inconveniences impacting network connectivity, lack of training about the use of digital health, and lack of digital health initiatives validation and policies. These results informed the development of the strategies to enhance the ulitization of digital health in early detection and treatment of pre-Eclampsia. Conclusion: For South Africa to succeed in achieving the Universal Health Coverage goals, midwifery practitioners should adopt digital health practices in clinical practice. The implementation of digital health should be reinforced and emphasized. Although there are more barriers to the implementation of digital health, the implementation of the developed strategies could possible facilitate a successful digital health use among midwives and gravid women and possible reduce perinatal and maternal mortalities and morbidities associated with lack of knowledge and access to healthcare information
Thesis (M.A. (Nursing)) -- University of Limpopo, 2023
Keywords: Strategies; Utilization; Early Detection; Gravid; Pre-Eclampsia; Treatment; Digital health; Midwifery practitioners; Preeclampsia; Midwifery; Uterus, Pregnant; Pregnant women